Opening the Curtains on Popular Practice: Kaichō in the Meiji and Taisho Periods - Mitchell, Matthew (Japanese journal of religious studies, 2023)
In this article I discuss the continuity and changes of displays of temple and shrine treasures (kaichō) in the Meiji and Taisho periods. I estimate the number and features of kaichō in these periods primarily using articles in the Yomiuri shinbun and Shinano mainichi shinbun newspapers. I discuss the ways that these displays intersected with aspects of the Meiji period, including changing laws and the expansion of a convenient transportation network. The newspaper articles are also an excellent source of information regarding the practice of these displays, including the functions of confraternities, continued attraction of sideshows (misemono), and use of these displays to pray for victory in Japan’s modern wars and the repose of its war dead.